Active perinatal care of preterm infants in the German Neonatal Network. Issue 2 (27th June 2019) - Humberg, Alexander; Härtel, Christoph; Rausch, Tanja K.; Stichtenoth, Guido; Jung, Philipp; Wieg, Christian; Kribs, Angela; von der Wense, Axel; Weller, Ursula; Höhn, Thomas; Olbertz, Dirk M.; Felderhoff-Müser, Ursula; et al.
Abstract : Objective: To determine if survival rates of preterm infants receiving active perinatal care improve over time. Design: The German Neonatal Network is a cohort study of preterm infants with birth weight <1500 g. All eligible infants receiving active perinatal care are registered. We analysed data of patients discharged between 2011 and 2016. Setting: 43 German level III neonatal intensive care units (NICUs). Patients: 8222 preterm infants with a gestational age between 22/0 and 28/6 weeks who received active perinatal care. Interventions: Participating NICUs were grouped according to their specific survival rate from 2011 to 2013 to high (percentile >P75), intermediate (P25–P75) and low (<P25) survival. We compared these survival rates with data in 2014–2016. Main outcome measures: Death by any cause before discharge. Results: Total survival increased from 85.8% in 2011–2013 to 87.4% in 2014–2016. This increase was due to reduced mortality of NICUs with low survival rates in 2011–2013. Survival increased in these centres from 53% to 64% in the 22–24 weeks strata and from 73% to 84% in the 25–26 weeks strata. Conclusions: Our data support previous reports that active perinatal care of very immature infants improves outcomes at the border of viability and survival rates at higher gestational ages. The high total number of surviving infants below 24 weeks of gestation challenges national recommendations exclusively referring to gestational age as the single criterion for providing active care. However, more data are needed before recommendations for parental counselling should be reconsidered. Trial registration: Approval by the local institutional review board for research in human subjects of the University of Lübeck (file number 08–022) and by the local ethic committees of all participating centres has been given.